The role of connexin40 in developing atrial conduction. Issue 8 (31st January 2014) - Benes, Jiri; Ammirabile, Grazia; Sankova, Barbora; Campione, Marina; Krejci, Eliska; Kvasilova, Alena; Sedmera, David
Abstract : Connexin40 (Cx40) is the main connexin expressed in the murine atria and ventricular conduction system. We assess here the developmental role of Cx40 in atrial conduction of the mouse. Cx40 deficiency significantly prolonged activation times in embryonic day 10.5, 12.5 and 14.5 atria during spontaneous activation; the severity decreased with increasing age. In a majority of Cx40 deficient mice the impulse originated from an ectopic focus in the right atrial appendage; in such a case the activation time was even longer due to prolonged activation. Cx40 has thus an important physiological role in the developing atria.